2019
DOI: 10.3390/agronomy10010019
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Effects of Zinc, Boron, Silicon, and Zeolite Nanoparticles on Confer Tolerance in Potato Plants Subjected to Salinity

Abstract: Salinity stress is a severe environmental stress that affects plant growth and productivity of potato, a strategic crop moderately sensitive to saline soils. Limited studies are available on the use of combined nano-micronutrients to ameliorate salinity stress in potato plants (Solanum tuberosum L.). Two open field experiments were conducted in salt-affected sandy soil to investigate plant growth, physiology, and yield of potato in response to soil salinity stress under single or combined application of Zn, B,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(80 citation statements)
references
References 94 publications
5
75
0
Order By: Relevance
“…Similar results were reported by Muymas et al (2015) who observed that lettuce fresh weight, dry weight, leaf number, width, and length had increased by applying chitin-rich residues. The less effect of compost on fresh weight of lettuce head and SPAD reading in this study might be due to its lower content of nutrients, as reported by Murakami et al (2011) and Mahmoud et al (2020).…”
Section: Effect Of Organic Fertilisers On Lettuce Growth and Productionmentioning
confidence: 50%
“…Similar results were reported by Muymas et al (2015) who observed that lettuce fresh weight, dry weight, leaf number, width, and length had increased by applying chitin-rich residues. The less effect of compost on fresh weight of lettuce head and SPAD reading in this study might be due to its lower content of nutrients, as reported by Murakami et al (2011) and Mahmoud et al (2020).…”
Section: Effect Of Organic Fertilisers On Lettuce Growth and Productionmentioning
confidence: 50%
“…An increase in salt content in the growing environment increases salt stress on plant growth. Salinity results in reduced yield because of the reduction in photosynthesis efficiency, chlorophyll, total protein, biomass, stomata closure, and increasing oxidative stress [ 7 , 8 , 9 ]. The salinity response varies from plant to plant, the stage of growth, and the salinity level.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the seeds are an excellent source of carbohydrates, minerals (calcium and iron), and vitamins (thiamin, tocopherols, niacin, and folic acid) [ 22 ]. Earlier reports have individually documented that zinc or PBZ, as cost-effective agents, have multiple biochemical functions in plant development under stressful conditions [ 14 , 23 , 24 ]. Conversely, their integrative application on inducing pea salt tolerance, to our knowledge, has not been documented and required more exploration.…”
Section: Introductionmentioning
confidence: 99%